Indonesian Legal Compliance with International Human Rights Law on Female Genital Mutilation - Fitriani, Nurul Fazrie; Trisnawati, Elvita (Faculty of Law, Universitas Negeri Semarang, 2023)
This paper examines the legal framework in Indonesia concerning Female Genital Mutilation (FGM) in light of its obligations under international human rights law. FGM persists in Indonesia despite legal prohibitions and international condemnation. Through an analysis of Indonesian laws, international human rights instruments, and relevant case studies, this study explores the extent to which Indonesian legislation aligns with international standards on FGM. Despite ratifying several human rights treaties, Indonesia lacks comprehensive legislation explicitly criminalizing all forms of FGM, leading to inconsistent enforcement and protection gaps for girls and women. Moreover, cultural and religious justifications often hinder effective legal action against FGM practitioners. This paper underscores the urgent need for Indonesia to strengthen its legal framework, ensure effective enforcement, and promote awareness of human rights principles to eliminate FGM fully. By addressing these gaps, Indonesia can uphold its international human rights obligations and safeguard the rights and dignity of girls and women.